Representation of Iran joining CEDAW in the reformist and conservative press: a sociological examination of competing arguments on women’s human rights in Iran - Hosseini Milani, Zahra (2020)
The matter of women’s rights has been one of the main battlegrounds between reformists and conservatives, the two major blocs in Iranian politics. This thesis is an empirical case study of arguments in the reformist and conservative press between 2000-2004 on the matter of Iran joining CEDAW - Convention on the Elimination of the Discrimination Against Women. It focuses on how CEDAW opponents and supporters in the reformist and conservative press position the issue of women’s human rights in relation to their religious values, political positions, and the international criteria on women’s human rights and cultural particularities - features that are unique to certain cultures.